Network meta-analysis comparing the efficacy of biologic treatments for achieving complete resolution of nail psoriasis. (3rd April 2022) - Reich, Kristian; Conrad, Curdin; Kristensen, Lars Erik; Smith, Saxon D.; Puig, Luis; Rich, Phoebe; Sapin, Christophe; Holzkaemper, Thorsten; Koppelhus, Uffe; Schuster, Christopher
Abstract: Background: Nail psoriasis (NP) is common and of high importance in patients with psoriasis. Complete resolution of NP at week 24‒26 is an unambiguous nail outcome accessible for indirect treatment comparison of biologics. Objective: To evaluate the comparative efficacy of approved biologics in achieving complete resolution of NP at week 24‒26. Methods: A network meta-analysis (NMA) was conducted to indirectly compare the efficacy of six biologics in achieving complete resolution of NP at week 24‒26 in patients with moderate-to-severe psoriasis and concomitant NP. Complete resolution of NP was defined as a score of zero on the Nail Psoriasis Severity Index (NAPSI), modified NAPSI (mNAPSI) or Physician's Global Assessment of Fingernails (PGA-F). Results: The probability of achieving complete resolution of NP was highest for ixekizumab (46.5%; 95% credibility interval [CrI] 35.1‒58.0; Surface Under the Cumulative RAnking curve [SUCRA] 97%), followed by brodalumab (37.0%; 17.0‒61.0; 79%), adalimumab (28.3%; 24.4‒32.4; 62%), guselkumab (27.7%; 21.1‒35.1; 58%), ustekinumab (20.8%; 10.2‒35.2; 37%), and infliximab (0.8%; 0.0‒8.9; 17%). Conclusion: In patients with moderate-to-severe psoriasis and concomitant NP, ixekizumab has the greatest likelihood among approved biologics of achieving complete resolution of NP at week 24‒26. Findings should be interpreted carefully because of inherent study limitations.